Peranan Kegiatan Majelis Ta'lim Al-Khoirot dalam Meningkatakan Pengajaran dan Ibadah di Ponorogo - Purnomo; Ganes Marsyanda Putri; M. Zainal Arif; Happy Susanto (MUADDIB Jurnal Kependidikan dan Keislaman, 2022)
The research used in this research is qualitative research with a descriptive approach. This research is limited to efforts to describe existing phenomena. The location of this research is Ponorogo Regency. The ta'lim assembly is a religious study organization, where the provision of studies can be carried out conditionally based on the agreement of the congregation with K.H Muslih Sujarno, the data sources used in this research are primary and secondary data sources, the data collection techniques used in this research are observation, interview and documentation techniques, as for the data analysis steps, namely data reduction, data presentation and drawing conclusions. The role of the ta'lim assembly is that this assembly provides a forum or place to seek knowledge, and media, material on religious jurisprudence, morals, knowledge of the Koran, knowledge of hadith, knowledge of monotheism, yellow book. Supporting factors are a strategic location, there is consumption, scheduled activities and there are ta'lim assembly administrators who are able to regulate the course of the ta'lim assembly's activities. Meanwhile, the inhibiting factors are lack of time discipline, both from the congregation and presenters or ustad, and the composition of the management of the Al-Khoirot ta'lim assembly is still limited. The author suggests that future researchers will be able to complete the shortcomings in this research and find the best, effective concept in accordance with the future era of development to realize quality Islamic religious education.